Trust or not to trust: Analyzing the effect of social media influencers on the consumer purchase intention mediated by consumer attitude - Almeda, Sabrina Maxine Valencia (Animo Repository, 2023)
This study aimed to investigate how social media influencers influence consumer buying behavior in Metro Manila. Influencer marketing has become an effective advertising strategy for brands and companies to promote their products through individuals who are recognized for their knowledge and content in a particular industry. The study focused on two types of influencers, Macro and Micro, to understand their impact on consumer buying intentions and how it was affected by the attitudes of individuals living in Metro Manila. The study used the convenience sampling technique for a total sample size of 385 respondents who are convenient and available to take the survey. The study used the source credibility model and para-social relationships to analyze the impact of social media influencers on consumer purchase intentions. The correlational and regression analysis conducted on the relationship between Social Media Influencer and Consumer Purchase Intention provided evidence that Social Media Influencers had a significant positive impact on consumer behavior. The analysis also revealed that the sub-variables of Social Media Influencers (Relevance, Resonance, and Reach) played an important role in shaping consumer behavior. The results of the study suggested that social media influencers played an important role in shaping consumer behavior, and businesses could leverage their power to improve customer acquisition and retention strategies. The study found that consumer attitudes acted as a mediator in the relationship between social media influencers and consumer purchase intention. The findings highlighted the importance of considering consumer attitudes as a factor in understanding the impact of social media influencers on consumer behavior. The results of this study would be beneficial for businesses and marketers in creating effective marketing strategies using social media influencers.